FUNCTIONAL CAPACITY OF THE TERRITORIAL COMMUNITY IN RELATION TO EDUCATION SECTOR MANAGEMENT - KOZIІ Olesia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Management of the educational sector of territorial communities of Ukraine in the context of decentralization has acquired a fundamentally new meaning, since local governments have received not only formal powers, but also actual responsibility for planning the educational network, financing, staffing, analytical support of decisions and ensuring equality of access to educational services. At the same time, practice shows a significant differentiation of the management capabilities of communities, which actualizes the need not for descriptive assessments, but for clear tools for diagnosing their functional capacity. The goal is to form a system for assessing the functional capacity of a territorial community in managing the educational sector based on the development of measurable indicators suitable for applied diagnostics. The material basis of the study was Ukrainian scientific publications on the issues of public education management, analytical materials of the OECD and the World Bank, regulatory legal acts of Ukraine in the field of education and local self-government. The research methodology included a system analysis to identify functional blocks of education management, induction and deduction to establish relationships between management powers, practices and results, as well as the logical structuring method to form a block model and its operationalization in the form of a system of measurable indicators. Approaches to understanding the functional capacity of communities are systematized and the feasibility of considering it as an integrated ability to implement a full management cycle in the field of education is substantiated. Functional capacity is structured according to key management blocks (normative and institutional, strategic, financial and budgetary, personnel, analytical, procurement, quality and equality of access, accountability and participation block) and these blocks are translated into a system of quantitatively measured indicators. The practical suitability of the proposed system for diagnosing management imbalances, comparative analysis of communities and formation of an evidence-based basis for management decisions in the field of local educational policy is proven. The results of the study can be used by local governments, community education management bodies, regional departments and analytical centers to conduct self-assessment of management capacity, justify strategies for the development of community education systems and develop targeted programs to improve the quality and accessibility of education.